Disseminated cutaneous herpes simplex infection in a patient with Crohn's disease under azathioprine and steroids: First case report and literature review. (1st April 2014) - Santos-Antunes, João; Abreu, Cândida; Magro, Fernando; Coelho, Rosa; Vilas-Boas, Filipe; Andrade, Patrícia; Lopes, Susana; Macedo, Guilherme
Abstract: Immunosuppressive treatments used in the management of Inflammatory Bowel Disease, namely steroids, thiopurines and anti-TNF drugs, raise the risk of acquiring opportunistic infections. However, most of these infections are mild and self-limited, not requiring specific therapy or suspension of the immunosuppressors. We report a case of disseminated cutaneous herpes simplex infection in a patient with Crohn's disease under steroids and azathioprine.